Emilie Oléron Evans, Transferts culturels et historiographie de l'art : le cas de Nikolaus Pevsner (1902-1983) - Émilie Oléron Evans (Appareil)
This thesis demonstrates how the works of art and architectural historian Nikolaus Pevsner (1902-1983), a British scholar of German origin, played a major part in the accession of the history of art and architecture to the status of an academic discipline in the United Kingdom in the 1930s and 40s. This case study, along with the various networks that played a part in his displacement from Germany to Britain in 1933, sheds a different light on current research on the history of émigré intellectuals, as it seeks to show that there is a latent conflict between the ideal of universalism in science and the national socio-cultural vectors at play in transnational displacements. Our research focuses on methodological, institutional and historiographical transfers that made Pevsner’s career into a milestone in the historiography of art, architecture and design. It tackles the main aspects of his contribution, from the issue of the Modern movement, through the use of the concept of space in the architectural discourse based on the principle of empathy (Einfühlung), to the exploration of the artistic production and the architectural heritage of Pevsner’s country of adoption. Our contention is that the role of an art historian as a mediator between his subject and society goes beyond the realm of academia. This thesis shows how Pevsner found a place in British culture as editor, broadcaster and art critic, while basing these activities on German models, and how these activities gradually transformed an interpreter of culture into a cultural institution.